Comparison of peripheral iridectomy methods for posterior chamber phakic intraocular lens implantation in patients with brown irides. Issue 1 (December 2016) - Wu, Yan; Han, Fei; Quan, Yan; Jiang, Wei; Zhang, Hengdi; Luo, Tao
Abstract Background We explore and compare the advantages and disadvantages of different operating methods for a peripheral iridectomy (PI) for phakic posterior chamber implantable contact lens (ICL) implantation in patients with dark-brown irides. Methods Forty-six patients completed this prospective comparative study. Neodymium: yttrium-aluminum-garnet (Nd:YAG) PI was performed in 15 patients (30 eyes) 2 weeks prior to surgery (YAG PI group). Surgical PI was performed in 17 patients (34 eyes) 2 weeks prior to the ICL implantation (preoperative PI group), and intraoperative PI was performed during ICL implantation in 14 patients (28 eyes) (intraoperative PI group). The postoperative recovery of visual acuity, intraoperative complications, operation duration, and patients' visual disturbances were compared. Results Compared with the preoperative BCVA, the uncorrected visual acuity (UCVA) at 1 week was markedly restored in the preoperative PI group (P  = 0.004). UCVA in the three groups of patients had all recovered well at 1 and 3 months after ICL implantation and were significantly better than the preoperative BCVA (allP  < 0.01). In the YAG PI group, iris bleeding occurred in nine eyes (30.0 %) and 14 eyes (46.7 %) had pigment dispersion; these values were significantly higher than those in the preoperative PI group (5.9 and 14.7 %, respectively, bothP  = 0.01). In the intraoperative PI group, elevated high intraocular pressure occurred in four eyes (14.3 %), and eight eyes (28.6 %) had varying degrees of pigment dispersion after ICL implantation. Conclusions For patients with dark-brown irides, surgical PI performed 2 weeks prior to the implantation facilitated better postoperative recovery of visual acuity. Trial registration Current Controlled TrialsISRCTN35178162 . Retrospectively registered March 4th, 2013.